Comprehensive molecular characterizations of stage I–III lung adenocarcinoma with tumor spread through air spaces - Ye, Ronghao; Yu, Yongfeng; Zhao, Ruiying; Han, Yuchen; Lu, Shun (Frontiers in Genetics, 2023)
Purpose: The aim of this study is to investigate integrative genomic spectra of stage I–III lung adenocarcinoma with tumor spread through air spaces (STAS). Methods: We retrospectively identified 442 surgically resected lung adenocarcinoma patients of pathological stage I–III in Shanghai Chest Hospital from January 2018 to February 2021. Surgically resected tissues were used for next-generation sequencing (NGS) with a panel of 68 lung cancer‐related genes to profile comprehensive molecular characterizations. Results: A total of 442 cases were analyzed, including 221 (50%) STAS-positive (SP) and 221 (50%) STAS-negative (SN) lung adenocarcinoma patients. In total, 440 cases (99.6%) were positive for the overall mutational spectrum, and the higher mutational genes were EGFR, TP53, KRAS, ALK, SMAD4, and ERBB2 (62%, 42%, 14%, 10%, 7%, and 7%, respectively). Compared with the SN population, there was significantly lower EGFR alteration in the single-nucleotide variant (SNV) mutation spectrum (52.5% vs 69.7%, p < 0.001) and significantly higher TP53 alteration in the SP population (49.8% vs 34.8%, p = 0.002). EGFR L858R missense mutation (19.5% vs 37.6%, p < 0.001) and ERBB2 exon 20 indel mutation (1.8% vs 5.9%, p = 0.045) were more frequent in the SN population. The detection rate of ALK fusion rearrangements in the SP population was significantly higher than that in the SN population (13.1% vs 2.3%, p < 0.001). In the analysis of signaling pathways, no significant difference was discovered between SP and SN patients. No difference in 1-year disease-free survival was observed between SP and SN patients in this study. Conclusion: Significant differences exist in stage I–III lung adenocarcinoma patients with STAS in molecular characterizations.